2022
DOI: 10.1021/jacs.2c03692
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Key Transient Inter-Catalyst Interactions in a Reductive Metallaphotoredox-Catalyzed Allylation Reaction

Abstract: Metallaphotoredox chemistry has recently witnessed a surge in interest within the field of synthetic organic chemistry through the use of abundant first-row transition metals combined with suitable photocatalysts. The intricate details arising from the combination of two (or more) catalytic components during the reaction and especially the inter-catalyst interactions remain poorly understood. As a representative example of a catalytic process featuring such intricacies, we here present a meticulous study of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 47 publications
2
30
0
3
Order By: Relevance
“…Fluorimetry revealed that HE, Cp 2 TiCl 2 , and Co‐1 could quench the fluorescence of 4CzIPN (Figure 6). The Stern–Volmer plot was found to deviate from linearity since 4CzIPN possesses both prompt fluorescence (PF) and thermally activated delayed fluorescence (TADF) [64–66] . Therefore, it is necessary from TCSPC data to determine their individual quenching rate constants in the two decay pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorimetry revealed that HE, Cp 2 TiCl 2 , and Co‐1 could quench the fluorescence of 4CzIPN (Figure 6). The Stern–Volmer plot was found to deviate from linearity since 4CzIPN possesses both prompt fluorescence (PF) and thermally activated delayed fluorescence (TADF) [64–66] . Therefore, it is necessary from TCSPC data to determine their individual quenching rate constants in the two decay pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative addition activates the allyl electrophiles to provide access to the nucleophilic Co­(II)/Ni­(II) π-allyl intermediate (after a subsequent redox event). This intermediate then is proposed to engage in additions to various electrophiles. ,,,, Understanding the intimate details of these steps will impact the further development of this emerging reaction class.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, to the best of our knowledge, to date, there has only been one study of the overall kinetics of dual Ni/photocatalysis: a report by Seeberger in 2020 on the acetoxylation of an aryl iodide, in which a homogeneous Ir­(ppy) 3 photocatalyst was compared with heterogeneous graphitic carbon nitride photocatalyst, using a calibrated in situ Fourier transform-infrared (FT-IR) method . A recent study by Kleij and co-workers of an organophotocatalyst/Co-catalyzed decarboxylative allylation also incorporated some bulk in situ FT-IR and ultraviolet–visible (UV-vis) kinetic measurements and modeling …”
Section: Introductionmentioning
confidence: 99%